Enhancement of Atorvastatin Tablet Dissolution Using Acid Medium - Kahtan j.Hasson (College of Pharmacy University of Baghdad, 2017)
In this study some generic commercial products of Atorvastatin tablets were evaluated by dissolution test in acid medium by comparing with that of parent drug Lipitor of Pfizer Company. Some of solubilizing agents were studied in formulation  of Atorvastatin tablet including;  surface active agent  and PEG 6000 .The most effective factor was the  use of PEG6000 in formulation of Atorvastatin tablet which improved the dissolution and the results of dissolution profile of formulated tablet in this work  was bioequivalent to that of Lipitor .The quantitative analysis of this work was performed by using reversed phase liquid chromatography and a proper mixture of  mobile phase which give a retention time for Atorvastatin about 6 minutes .